Bicycle tourism in Hungary - Kormosné Koch, Krisztina (Applied Studies in Agribusiness and Commerce, 2013)
Side by side with the revaluation of a health-oriented lifestyle various kinds of axtive leisure activities and active tourism in particular have been gaining ground. Cycling, which is popular not only as a leisure time tourism activity but mainly within settlements, also as an environmentally-friendly and up to a certain extent, a highly practicable means of transport mainly in towns and cities in WesternEurope, has a privileged position within active tourism (SALAMIN, 2010). This article wishes to present the situation of bicycle tourism, the factors influencing the demand for it and the opportunities for and possibilities of improving it within Hungary by providing an evaluative analysis of the relevant sources of the technical literature. The most important finding of this secondary research-based study is that there is an increasing contention both internationally and within certain regions of tourist interest within Hungary although there is no detailed information available as regards the latter. Success on the market can only be achieved by following the good practices of internationally developed tourist destinations and by a concerted development and improvement of the infrastructure, services and target-group oriented marketing activities as well as attractions.